Prurigo in People Living with HIV (PLHIV) in Cotonou, Benin - ADEGBIDI, HUGUES DANIEL GBADEBO; AKPADJAN, GBEMAWONMEDE FABRICE (My University, 2012)
Prurigo is a dermatosis especially prevalent among patients infected with HIV. The objective of this work was to study the clinical and epidemiological features of prurigo in a population infected with HIV in Cotonou. This was a cross-sectional study on people living with HIV (PLHIV) in a center of care over a period of six months. The data were collected employing a survey form and were processed and analyzed using Epi Info 6. 117 People Living with HIV (PLHIV) were seen during the study period. Prurigo was present in 53.80% of patients and represented the most common skin disease (34.16%). The maculo-papular lesion was the most frequent, representing 36.40% of the clinical forms. The most frequent sites were the lower and upper limbs followed by the trunk. The prevalence of prurigo was statistically higher in patients with a low CD4 count.
Keywords: Africa; AIDS; ART; HIV; Prurigo